2011
DOI: 10.1007/s11182-011-9572-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural-acoustic analysis of a nanodispersed magnetic fluid

Abstract: 538.951Results of investigations into the dispersed composition of a magnetic fluid based on the measured dependence of the amplitude of the acousto-magnetic effect on the magnetic field strength are considered. The results obtained are compared with the data of atomic force microscopy and magneto-granulometric analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…We may consider it a natural peculiarity of the dashed and solid curves that the first one is in good agreement with experiment in small magnetic fields and the second one is in good agreement with experiment in fields close to saturating fields. The significant discrepancy between the theoretical, β ξ (Н), and experimental, β(H), values in the region of medium magnetic fields is primarily due to the fact that the employed model disregards the particle size distribution [13]. Figure 6 shows the magnetization curve β М (Н) (dashed rhombs) in relative units and the AME curve β(Н) (triangles).…”
Section: The Results Of Measurement and Their Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We may consider it a natural peculiarity of the dashed and solid curves that the first one is in good agreement with experiment in small magnetic fields and the second one is in good agreement with experiment in fields close to saturating fields. The significant discrepancy between the theoretical, β ξ (Н), and experimental, β(H), values in the region of medium magnetic fields is primarily due to the fact that the employed model disregards the particle size distribution [13]. Figure 6 shows the magnetization curve β М (Н) (dashed rhombs) in relative units and the AME curve β(Н) (triangles).…”
Section: The Results Of Measurement and Their Analysismentioning
confidence: 99%
“…Analysis of the relative amplitude of the induced EMF as a func tion of the magnetic field strength, among other gran ulometric methods [11], is a promising method for studying the geometric and magnetic parameters of magnetic nanoparticles [12][13][14]. However, the physi cal nature of the AME and peculiarities of the interac tion of physical fields inherent in this effect remain ununderstood.…”
Section: Introductionmentioning
confidence: 99%
“…In several other works, researchers considered the influence of temperature, the concentration of MNPs, the frequency of sound vibrations, and the presence of aggregates [ 169 , 170 , 171 ] on the speed of sound and its absorption coefficient in magnetic fluid. The work of Sokolov [ 172 , 173 ] present the results of studies on magnetic fluid using acoustic spectroscopy in the frequency range from 3 MHz to 50 MHz, establishing the relaxation nature of ultrasound attenuation in MF.…”
Section: Physical Properties and Structure Of Magnetic Fluidsmentioning
confidence: 99%
“…Although MRFs have been widely studied for vibration control applications, limited studies have been conducted to investigate their acoustical properties and explore their potential for noise control applications. Polunin et al [ 16 , 17 ] performed the experimental studies of the acousto-magnetic effect (AME) in a magnetic fluid and investigated the dispersed composition and magnetic and geometrical parameters of magnetic fluid nanoparticles based on the AME. Rodríguez-López et al [ 18 , 19 ] analyzed the effects of uniformity, direction, and intensity of the magnetic field on the attenuation of ultrasonic elastic waves in MRF, and the results showed that the sound attenuation increased with an increase in the magnetic intensity until saturation was reached.…”
Section: Introductionmentioning
confidence: 99%